Skeletal muscle munc18c and syntaxin 4 in human obesity - Bergman, Bryan C; Cornier, Marc-Andre; Horton, Tracy J; Bessesen, Daniel H; Eckel, Robert H (Nutrition & metabolism, 2008)
Animal and cell culture data suggest a critical role for Munc18c and Syntaxin 4 proteins in insulin mediated glucose transport in skeletal muscle, but no studies have been published in humans. We investigated the effect of a 12 vs. 48 hr fast on insulin action and skeletal muscle Munc18c and Syntaxin 4 protein in lean and obese subjects. Healthy lean (n = 14; age = 28.0 +/- 1.4 yr; BMI = 22.8 +/- 0.42 kg/m2) and obese subjects (n = 11; age = 34.6 +/- 2.3 yr; BMI = 36.1 +/- 1.5 kg/m2) were studied twice following a 12 and 48 hr fast. Skeletal muscle biopsies were obtained before a 3 hr 40 mU/m2/min hyperinsulinemic-euglycemic clamp with [6,6-2H2]glucose infusion. Glucose rate of disappearance (Rd) during the clamp was lower in obese vs. lean subjects after the 12 hr fast (obese: 6.25 +/- 0.67 vs. lean: 9.42 +/- 1.1 mg/kgFFM/min, p = 0.007), and decreased significantly in both groups after the 48 hr fast (obese 3.49 +/- 0.31 vs. lean: 3.91 +/- 0.42 mg/kgFFM/min, p = 0.002). Munc18c content was not significantly different between lean and obese subjects after the 12 hour fast, and decreased after the 48 hr fast in both groups (p = 0.013). Syntaxin 4 content was not altered by obesity or fasting duration. There was a strong positive relationship between plasma glucose concentration and Munc18c content in lean and obese subjects during both 12 and 48 hr fasts (R2 = 0.447, p = 0.0015). Significant negative relationships were also found between Munc18c and FFA (p = 0.041), beta-hydroxybutyrate (p = 0.039), and skeletal muscle AKT content (p = 0.035) in lean and obese subjects. These data indicate Munc18c and Syntaxin 4 are present in human skeletal muscle. Munc18c content was not significantly different between lean and obese subjects, and is therefore unlikely to explain obesity-induced insulin resistance. Munc18c content decreased after prolonged fasting in lean and obese subjects concurrently with reduced insulin action. These data suggest changes in Munc18c content in skeletal muscle are associated with short-term changes in insulin action in humans.